Branding UMKM dalam Pengembangan Wisata Budaya Patehan Yogyakarta - Rahmawaty, Penny; Lina; Arum; Alteza, Muniya; Gallen GP, Mahendra Ryansa (Politeknik Negeri Jember, 2024)
Yogyakarta as a tourist destination has a cultural heritage in the form of an imaginary Philosophical Axis consisting of the Golong-Gilig Monument, Kraton, and Krapyak Stage which are in a straight line. Patehan Village is one of the areas in the Keraton area. Patehan is the part of the palace which is responsible for preparing drinks, especially tea, along with all the equipment for Yogyakarta Palace activities, starting from traditional ceremonies to meeting daily routine needs. Patehan is supported by the existence of various businesses, namely culinary, transportation, trade, and the creative economy. However, no special place sells and serves palace-style brewed tea. A change in mindset is needed to become an entrepreneur with a far-sighted vision. Apart from that, they also do not realize the importance of product branding as a competitive advantage. The aim of Community Service is the importance of changing the entrepreneurial mindset and the importance of product branding. The form of activity is training and business assistance. The outcomes of community service activities are the importance of MSME actors changing their entrepreneurial mindset, having product brands, and promoting products through social media for them to increase the number of domestic and foreign tourist visits